The degradation of traditional english book reading habits among teenagers as an impact of digital culture influence - Mulyani, Mulyani; Imran, Imran; Muhammad Arif Sanjaya; Nayla Faradilla; Nadhira, Nadhira (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to explicitly determine how digital culture influences and contributes to the degradation of traditional English book reading habits among teenagers in Alue Pineung Village, East Langsa District. The rise of digital media in the era of Industry 5.0 has transformed the way adolescents access information and acquire knowledge. Teenagers have become accustomed to brief, fast-paced digital content, which has gradually displaced the habit of reading physical books. To examine this phenomenon, the study employed a descriptive qualitative method using observations, interviews, and questionnaires as data collection techniques, and the data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that digital culture has significantly contributed to the decline in teenagers’ interest in reading printed English books. Most respondents prefer digital reading materials because they are more practical, faster to access, and visually appealing. The contribution of this research lies in providing a deeper understanding of how digital exposure reshapes literacy behavior in rural contexts, highlighting the shift from deep, reflective reading to more superficial and instant information consumption. This study offers valuable insight for educators and policymakers to design literacy strategies that balance digital engagement with the preservation of traditional reading practices.